Biomedical Literature Mining - Kumar, Vinod D.; Tipney, Hannah Jane (Springer New York, 2014)
Biomedical Literature Mining,  discusses the multiple facets of modern biomedical literature mining and its many applications in genomics and systems biology. The volume is divided into three sections focusing on information retrieval, integrated text-mining approaches, and domain-specific mining methods. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Biomedical Literature Mining  is  designed as a useful bioinformatics resource in biomedical literature text mining for both those long experienced in, or entirely new to, the field
Keywords: Life Sciences; Bioinformatics; Systems Biology; Computer Appl. in Life Sciences; Life sciences; Systems biology; Computational biology; Text Mining; Biomedizin